PENGARUH PERBEDAAN JENIS WARNA CAHAYA LAMPU DAN KEPADATAN KANDANG TERHADAP PERSENTASE KARKAS DAN BOBOT ORGAN VISCERAL PADA PEMBESARAN BUJuduRUNG PUYUH (Coturnix coturnix japonica) JANTAN - Ertika Fitri Lisnanti; Sunda ri (Universitas Islam Kadiri, 2016)
Various lighting program which consists of light color, light period and light intensity can increase the biological functions that directly stimulate quail growth. The purpose of this research was to find the influence of light color and cage density to male quail carcass persentage and visceral organ weight. Method was used in this reseach was Completely Randomized Design with factorial pattern containing two factors were light color (white, yellow, green) and cage density (40 male quails/m2and60 male quails/m2). The result showed that green light with cage density 60 male quails/m2give the significant effect on carcass persentage and visceral organ weight compare with white and yellow light with cage density 40 male quail/m2. Hovewer, green light give relaxing effect that could reduce stress respond to male quails